Hubungan Hipertensi dengan Kejadian Gagal Ginjal Kronik di RSUD DR. Djasamen Saragih Kota Pematang Siantar Tahun 2020 - Mai Debora Gultom; Mondastri Korib Sudaryo (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2023)
Background: Chronic renal failure (CRF) had became a concern because of the increasing globally for incidence, prevalence, and mortality and hypertension was one of the main causes of CRF. magnitude of the risk of hypertension with chronic renal failure. This study aims to assess the magnitude of the risk of hypertension with chronic kidney failure at Dr. Djasamen Saragih City of Pematang Siantar.Methods: This research was an analytic observational study with a case control design. The research subjects were 260 kidney failure patients who were treated at RSUD Dr. Djasamen Saragih Kota Pematang Siantar with as many as 52 cases of patients diagnosed with chronic kidney failure by doctors who can be seen from medical records. As many as 208 hospital controls were patients without CRF (gastritis, gastroenteritis, hernia, and trauma or minor infections). The inclusion criteria of the study subjects were ≥ 18 years of age and had completed medical record data. The exclusion criteria for study subjects were if they had a history of kidney transplantation or a history of kidney transplantation and patients with incomplete medical records.Results: the results of the analysis of bivariate hypertension variables, patients aged > 45 years, patients with diabetes, patients with anemia, patients with gout, and patients with a history of kidney stones showed a relationship with the incidence of kidney failure. The multivariate results showed that the incidence of hypertension in patients with chronic renal failure was 5.52 times higher than those without chronic renal failure with an OR of 5.52 (95% CI: 2.10-14.53).Conclusion: Hypertension has a relationship with the incidence of chronic renal failure with an OR value of 5,52 (95% CI: 2.10-14.53).